Waterloo : Napoleon's last campaign - Hibbert, Christopher, 1924-2008. (Hertfordshire SG : Wordsworth Editions, 1998)
This book is divided into three parts: the first studies Napoleon and his rise to power, the second describes Wellington and the allied armies, while the third reconstructs the battle of Waterloo. A final summary investigates the significance of the battle on world history.
Includes bibliographical references (pages 267-274).
Keywords: Napoleon -- I, -- Emperor of the French, -- 1769-1821.; 1815; Waterloo, Battle of, Waterloo, Belgium, 1815.; Belgium -- Waterloo